Enhanced efficacy of sequential administration of fosfomycin and linezolid against methicillin-resistant Staphylococcus aureus - Chen, Zaixing; Ai, Qin; Zheng, Shuai; Chen, Ziyan; Wang, Sailan; Zhang, Na; Liu, Huiping; Liu, Yanyan; Li, Jiabin; Huang, Xiaohui (Frontiers in Microbiology, 2025)
The aim of this study was to assess the superiority of sequential administration of fosfomycin and linezolid in combination on the efficacy of methicillin-resistant Staphylococcus aureus (MRSA). The antimicrobial activity was assessed using static and dynamic bactericidal assays, along with pharmacokinetics/pharmacodynamics in vitro simulation models. Transmission electron microscopy (TEM) was employed to observe ultrastructural changes in MRSA cell walls following both sequential and concomitant dosing strategies. The results indicated that in the static time-kill assay, at MIC levels (fosfomycin at 4–8 mg/L and linezolid at 2–4 mg/L), the combination effectively inhibited MRSA growth under both concurrent and sequential administration; however, the sequential dosing regimen exhibited significantly greater bactericidal activity. Similarly, in the dynamic sterilization test conducted at clinically relevant doses (linezolid 600 mg and fosfomycin 2 g), a comparable trend was observed, further supporting the superior efficacy of sequential administration. TEM analysis further revealed that sequential dosing caused more extensive damage to the bacterial cell wall and nucleus compared to concomitant administration. These findings suggest that sequential administration of fosfomycin and linezolid enhances in vitro efficacy against MRSA and may provide an improved approach for managing complicated and drug-resistant infections.